THE INTEGRATION OF LITERATURE, CULTURE AND ART IN LANGUAGE TEACHING (Konferensiyalar | Conferences, 2024)
In today's developing world, the increasing interest in language learning requires special attention to a number of issues in language teaching. This article examines the interdependence of literature, art and culture and their specific value in the process of language teaching.